Rare compound heterozygous variants of LAMB3 and histological features of enamel and oral mucosa - Li, Fang; Yu, Miao; Fan, Zhuangzhuang; Wu, Junyi; Tian, Hua; Feng, Hailan; Liu, Yang; Liu, Haochen; Han, Dong (Frontiers in Physiology, 2022)
Junctional epidermolysis bullosa (JEB) is a group of autosomal recessive disorders characterized by amelogenesis imperfecta (AI) and fragility of the skin and mucous membranes. The purpose of this study was to identify pathogenic gene variants and investigate the phenotypic characteristics of abnormal enamel structure and mucocutaneous lesions in a patient with JEB. Clinical examination of the patient revealed hypoplastic AI, skin lesions, and oral ulcers, whereas her parents were normal. Whole-exome sequencing (WES) and cDNA cloning identified compound heterozygous variants of LAMB3 in the proband: c.125G>C in exon 3, c.1288+1G>A in intron 11, and c.1348C>T in exon 12. Among these, c.125G>C was inherited from her father, and the other two variants were inherited from her mother. Functional prediction indicated that the variants might change protein structure and cause disease. Scanning electron microscopy (SEM) examination of the primary and permanent teeth revealed abnormal enamel morphology and microstructures. Hematoxylin-eosin (HE) and immunofluorescence (IF) staining showed significantly abnormal and disorganized epithelial cells in the gingival mucosa. Our results showed that this was a case of intermediate JEB1A (OMIM #226650) with autosomal recessive inheritance. The proband carried rare compound heterozygous variants of LAMB3. Our results broaden the variant spectrum of the LAMB3 gene and JEB cases. Moreover, this is the first study to identify histological malformations of the primary teeth and oral mucosa in LAMB3-related patients.